Impact of brand awareness, brand equity and brand slogan towards product advertisement: a case study in advertising industry / Rohani Jangga ... [et al.] - Jangga, Rohani; M Ali, Norlina; Shahwir, Siti Farrah; Kamarolzaman, Noraishah; Mohd Hatta, Hazieqa Syabilla (UiTM Cawangan Johor, 2020)
Brand awareness is a company's competitive advantage and is a part of a marketing strategy which helps to spread information about a selected company and their products and services. It is crucial that customers remember and recognize a favorite brand every time they want to buy a product. In today's fast evolving marketing scenario, technology has been used to capture a wider target market as almost all product information is at the fingertips of consumers. Through good marketing campaigns such as using social media apps, strong brand awareness can be created, and customer loyalty maintained. Technically, brand slogan is about ideas and themes of the company. Sometimes, the name of the company does not represent the products of the company. Thus, the slogan will help users understand more about the products of the company. In addition, brand slogan helps each company to highlight the unique value propositions which means every tagline has its own meaning. Hence, the slogan that will help the company to reflect its mission statement is short and catchy to attract customer's attention and can be understood clearly. Brand equity is the value of the brand itself which means it can be described as having a well-known brand name, able to generate revenue which can lead to brand recognition. Brand equity is crucial in increasing profit margins, create customer loyalty, expand business opportunities and competitive advantage.